2015
DOI: 10.1115/1.4030048
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol to Address User Behavior in the Eco-Design of Consumer Products

Abstract: International audienceToday, it is difficult to integrate the use phase optimization of consumer products into eco-design methodologies. Current eco-design approaches are in fact mainly focused on improving the technological performance of products while it has been proven that users behavior plays an important role in the overall environmental performances of products. This paper deals with the need to address the notion of user experience and behavior in the design process of today's low-complexity consumer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Montazeri, et al [21] created napkin dispensers that displayed the quantity of napkins used, and validated in a field study each design's effectiveness at reducing consumption. Cor and Zwolinski [7] tested four coffee makers intended to encourage electricity conservation. They found that the eco-feedback design (which reported energy consumed while making coffee) and the goal setting design (which provided a target value for energy consumption) were perceived as more useful and less intrusive than a written-information design (which offered instructions for turning off the coffee maker) or a smart design (which switched off the coffee maker automatically).…”
Section: Design For Sustainable Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Montazeri, et al [21] created napkin dispensers that displayed the quantity of napkins used, and validated in a field study each design's effectiveness at reducing consumption. Cor and Zwolinski [7] tested four coffee makers intended to encourage electricity conservation. They found that the eco-feedback design (which reported energy consumed while making coffee) and the goal setting design (which provided a target value for energy consumption) were perceived as more useful and less intrusive than a written-information design (which offered instructions for turning off the coffee maker) or a smart design (which switched off the coffee maker automatically).…”
Section: Design For Sustainable Behaviormentioning
confidence: 99%
“…More specifically, we examine eco-feedback designs [6] which aim to promote pro-environmental behavior in users by making them aware of their resource consumption and its consequential environmental impact. Compared to other strategies of designing for sustainable user behavior such as "behavior steering" which encourages behavior change via embedded product constraints or affordances, and "smart" designs which automatically take actions to enforce behavior change, eco-feedback has the advantages of being less intrusive [7], easier to implement [8], and has higher potential to raise users' environmental awareness [9].…”
Section: Introductionmentioning
confidence: 99%
“…MacDonald and She conducted an in lab experiment mimicking a realistic purchasing scenario to reveal user preferences for the sustainable trigger features of toasters [22]. Cor and Zwolinski tested the effectiveness of four coffee maker designs in encouraging energy and water conservation behaviors as well as acceptance by users [23]. Sohn et al tested the immediate user reaction to design attributes of products that promote pro-environmental behaviors [24].…”
Section: Related Workmentioning
confidence: 99%
“…Four versions of each of the products above were designed to include each of the following eco-feedback prompts: These design prompts were chosen based on existing ecofeedback design literature cited in this paper [23,24,26]. They were created with the intention of displaying different levels of data quantitativeness and emotion evocation.…”
Section: Eco-feedback Promptsmentioning
confidence: 99%
“…The consumption prediction is closer to reality compared to the standard averaged energy consumption profiles. Cor et al (2014), Cor & Zwolinski (2015) developed a protocol to integrate user behaviour into the ecodesign of low-complexity consumer products. The protocol is composed of the following steps: (1) identify critical environmental aspects in use; (2) support designers to select a design strategy for sustainable behaviour after analysis of the use phase; and (3) test the selected strategy with product-in-use observations.…”
Section: Confirmation With the Literaturementioning
confidence: 99%